Comparative effects of continuous cultivation of seven crop combinations on soil physicochemical properties in two soils of different land use history in eastern Nigeria - Asadu, C.; Dixon, A.G.O. (Informa UK Limited, 2002)
Changes in 29 soil physicochemical properties resulting from crop cultivation in newly cleared virgin forest were compared with those from previously cultivated land. The aim was to assess the effects of the selected common crop combinations on the soil properties so as to obtain the best option for soil fertility enrichment in each location. The crops selected were those commonly grown by the local farmers. They included sole crops of cassava, yam, maize and pigeon pea, as well as a combination of all the four crops. Others were cassava+maize+pigeon pea and cassava+pigeon pea. Both the sole and crop combinations (which were the treatments) were grown in a randomized complete block design in three replicates in the two locations for two years. Changes in soil properties at 0–20 cm and 20–40 cm depths were monitored for the period. The soils were sampled at the beginning of each cropping season from 1998 to 2000.The pedogenic properties obtained from the diagnostic horizons were used to classify both soils as Rhodic Kindiustalfs (Haplic Lixisols). However, the differences in 19 of the properties at 0–40 cm depth were significant (p≤0.05) between the two locations ab initio. Sixteen of these properties were considered to be better in the forestland agronomically. Depth variations did not influence many of the properties significantly, especially between 1999 and 2000. The effects of crop combination were significant (p≤0.05) on physical properties such as the silt content, the total porosity at the forest location; clay content, bulk density, macroporosity, and hydraulic conductivity at the previously cultivated soil (UNN site). The chemical properties significantly (p≤0.05) affected by crop combination were exchangeable calcium (Ca) and total exchangeable bases at the forest; organic matter, exchangeable potassium (K), total exchangeable acidity, and available phosphorus (P) at the UNN site. Among the properties only the clay content, macroporosity and organic matter seemed to show significant differences between the plots allocated to the different crops and mixtures at the UNN site at the beginning in 1998. Within the short period of the study, there appeared to have been substantial improvements in some properties, especially at 0–20 cm depth, relative to their 1998 values. The changes were generally more in the UNN site than at the forest. The changes were adduced to be facilitated by tillage, as the soils were just brought under cultivation from the forest and fallow conditions. This is because the crop effects were less between 1999 and 2000. However, the improvements in some of the properties suggest that some of the crop combinations were capable of reducing soil fertility loss in the area.